Entrepreneurship model for staff corporate education in a multinational corporation - Avdeeva, Tat’yana; Авдєєва, Тетяна; Hrabylnikova, Olena; Грабильникова, Олена; Prykhodko, Olga; Приходько, Ольга; Prykhodko, Igor; Приходько, Ігор Павлович; Ohdanskiy, Kyrylo; Оданський, Кирило (Allied Business Academy, 2019)
The external and internal factors influencing the entrepreneurship education of the personnel in the TNCs of Poland were revealed. The national peculiarities of the economic behaviour of Polish personnel in companies, in particular, the intensive development of all competencies and rapid entrance to the international arena were revealed. A comparative analysis of entrepreneurship education of personnel in TNCs in Germany and Poland has been carried out according to three criteria: the system of training and regulatory support; the system of corporate education of TNCs, scientific and methodological support of this system. Виявлено зовнішні та внутрішні чинники впливу на підприємницьку освіту персоналу в ТНК Польщі. Виявлено національні особливості економічної поведінки польського персоналу в компаніях, зокрема, інтенсивний розвиток усіх компетенцій та швидкий вихід на міжнародну арену. Проведено порівняльний аналіз підприємницької освіти персоналу в ТНК Німеччини та Польщі за трьома критеріями: система навчання та нормативне забезпечення; система корпоративної освіти ТНК, науково-методичне забезпечення цієї системи.
Модель підприємництва для корпоративного навчання персоналу в багатонаціональній корпорації
Keywords: Entrepreneurship Education; Навчання підприємництву; Corporate Training Centre; Корпоративний навчальний центр; Dual System of Professional Development; Подвійна система професійного розвитку; Transnational Corporations; Транснаціональні корпорації; Cultural Distance; Культурна дистанція; Global Business; Глобальний бізнес